O CÂNONE NA HISTÓRIA DA LITERATURA BRASILEIRA - Barbosa, João Alexandre (Organon, 2012)
This essay, whose title is a metaphor for what is imaginary in the questionof canons, is about brazilian literary canon such it was built by succesive literaryhistories since the romantic movement. Also as sugested by its title, the mainassertion is that each reader has his own canon but anyway imposed by readingsexperiences. Without defending any specific canon, the essay open the possibility ofthinking in the canons formation in accordance with several ways of institutionalteachings of literature including and foremost the different histories of literature.